Transcriptome analysis of Bipolaris sorokiniana - Hordeum vulgare provides insights into mechanisms of host-pathogen interaction - Basak, Poulami; Gurjar, Malkhan Singh; Kumar, Tej Pratap Jitendra; Kashyap, Natasha; Singh, Dinesh; Jha, Shailendra Kumar; Saharan, Mahender Singh (Frontiers in Microbiology, 2024)
Spot blotch disease incited by Bipolaris sorokiniana severely affects the cultivation of barley.The resistance to B. sorokiniana is quantitative in nature and its interaction with the host is highly complex which necessitates in-depth molecular analysis. Thus, the study aimed to conduct the transcriptome analysis to decipher the mechanisms and pathways involved in interactions between barley and B. sorokiniana in both the resistant (EC0328964) and susceptible (EC0578292) genotypes using the RNA Seq approach. In the resistant genotype, 6,283 genes of Hordeum vulgare were differentially expressed out of which 5,567 genes were upregulated and 716 genes were downregulated. 1,158 genes of Hordeum vulgare were differentially expressed in the susceptible genotype, out of which 654 genes were upregulated and 504 genes were downregulated. Several defense-related genes like resistant gene analogs (RGAs), disease resistance protein RPM1, pathogenesis-related protein PRB1-2-like, pathogenesis-related protein 1, thaumatin-like protein PWIR2 and defensin Tm-AMP-D1.2 were highly expressed exclusively in resistant genotype only. The pathways involved in the metabolism and biosynthesis of secondary metabolites were the most prominently represented pathways in both the resistant and susceptible genotypes. However, pathways involved in MAPK signaling, plant-pathogen interaction, and plant hormone signal transduction were highly enriched in resistant genotype. Further, a higher number of pathogenicity genes of B. sorokiniana was found in response to the susceptible genotype. The pathways encoding for metabolism, biosynthesis of secondary metabolites, ABC transporters, and ubiquitin-mediated proteolysis were highly expressed in susceptible genotype in response to the pathogen. 14 and 11 genes of B. sorokiniana as candidate effectors were identified from susceptible and resistant host backgrounds respectively. This investigation will offer valuable insights into unraveling the complex mechanisms involved in barley-B. sorokiniana interaction.